2014
DOI: 10.1039/c4cc05905k
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing a highly unstable frustrated Lewis pair: dihydrogen cleavage by a thermally robust silylium–phosphine adduct

Abstract: The thermally robust silylium complex [iPr3Si-PtBu3](+)[B(C6F5)4](-) (1) activates H2/D2 at 90 °C (PhCl); no evidence for dissociation into the separated Lewis pair is found. DFT calculations show H2 cleavage proceeds via Si-P bond elongation to form an encounter complex directly from the adduct, thus avoiding the non-isolable iPr3Si(+)-PtBu3 FLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 39 publications
1
60
0
1
Order By: Relevance
“…[86][87] In related work, Ashley et al 88 showed that silylium-phosphine adducts activate H 2 under elevated temperatures, presumably via the thermal generation of an FLP. Müller and co-workers 89 also developed a silylene/silylium FLP (Scheme 5), demonstrating that it too activates H 2 although the protonated silylene rearranges to a hydrogen-bridged disilyl cation.…”
Section: Silicon-based Flpsmentioning
confidence: 98%
“…[86][87] In related work, Ashley et al 88 showed that silylium-phosphine adducts activate H 2 under elevated temperatures, presumably via the thermal generation of an FLP. Müller and co-workers 89 also developed a silylene/silylium FLP (Scheme 5), demonstrating that it too activates H 2 although the protonated silylene rearranges to a hydrogen-bridged disilyl cation.…”
Section: Silicon-based Flpsmentioning
confidence: 98%
“…38 Further, Ashley et al reported on a phosphine stabilized silylium species able to cleave H 2 . 39 We report herein the formation of novel intramolecular FLP-CO 2 adducts by reaction of CO 2 with nitrogen stabilized silyl cations. These systems exhibit excellent catalytic activity in the hydroboration of CO 2 , and the catalytic involvement of FLP-CO 2 adducts is addressed, based on mechanistic experimental, and DFT investigations (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…As we know that a FLP contains both Lewis acid and base centers, and the most common active Lewis pairs are B/N, B/P, Al/N and Al/P. Furthermore, a cationic Lewis acid component has also been extended to silicon1516, carbon17, in ref. 9 and even the transition-metal (Zr1819 and Ti20) complexes, while the Lewis base component has been extended to O 9 , carbenes21, ethers22, ketones23, and sulfides24.…”
mentioning
confidence: 99%